Linking taxation and social protection: Evidence on redistribution and poverty reduction in Ethiopia - Hirvonen, Kalle; Mascagni, Giulia; Roelen, Keetie (John Wiley & Sons, 2018)
Although redistribution results from the simultaneous effects of taxes and transfers, analyses of their distributional effects in low‐income countries have largely been undertaken from singular perspectives. This article jointly assesses the distributional effect of taxes and transfers (through social protection) using Ethiopia as a case study. We find that Ethiopia's flagship social protection programme is more effective than income taxation in achieving poverty reduction, while neither policy achieves a sizeable reduction in overall inequality. We also find that Ethiopia does not currently have the capacity to close the poverty gap or to fully fund its main safety net programme using domestic income sources alone.